Universals from the Viewpoints of Shahab Al-Din Suhrawardi and Duns Scotus - Aliasghar Sharbati; Saeed Rahimian (Comparative Theology, 2022)
The philosophical analysis of universals needs to clarify two terms: the world and the mind. If we can understand the relation between these two, it is possible to answer two questions. First, what are universals? And second, how to make universals? The present research aims to compare universals from the viewpoint of Shahab Al-Din Suhrawardi (1154-1191 CE) and Duns Scotus (1266-1308 CE). Both of them follow the Greek legacy and are under Abrahamic religions.They distinguish between common and special features of the world when they describe it. In Islamic philosophy, these features are called "existence" and "quiddity". But Suhrawardi, by the revival of the system of light, recognizes them as the "light" or the "being". He distinguishes between existence (Wojoud) and being (Maujoud). This distinction is linguistic and ontological. Existence is always in the mind while the being is found in the world outside of the mind. He believes that the specific feature of the world is shown by the beings (Maujoudat). But Suhrawardi does not search for the common feature in existence. He explains that feature by the light (Nour) and the layout of the system patterned by the lights (Anwar). This cosmos system includes the longitudinal and widthways orders. The results of the two orders are two versions of universals.The first version (it could be named the Aristotelian version) belongs to the longitudinal dimension. This version is presented by mind functions. Suhrawardi is among a few Muslim Philosophers that highlights the mind’s function. He believes that the mind has an active and a passive role. The passive one is only a place for perceptions and memories, but its activeness or agency is introduced by the intellect-mind relation. The intellect-act (ontological and epistemological) relation is limited by the mind.Suhrawardi discusses platonic ideas in a widthways order. It results from the second version. But it is important to mention that Suhrawardi’s reading is a wider view of the universals. Suhrawardi’s reading of platonic ideas explains upward and downward lights. The upward light is the result of illumination (Ishraq) and the downward light is the result of observation (Mushahadah). The upward one expresses the Aristotelian universals, and the downward one shows the platonic version.On the other hand, in the medieval period, the term “common nature” express a major problem of universals. This term originates from the Natural Universals of Avicena. The Avicenian concept was so ambiguous, i.e, what he describes is not in the world nor the mind. So, medieval philosophers and commentators had a problem with Avicenna’s quote. The problem was how to interpret universals. Avicenna confirms that the term universal is neither in the world nor in the mind, that is, it has no necessity.Scotus confronts such a strange ontological state. He doesn’t make the Natural Universal in the mind or in the world; rather, he tries to go out of it from its contradictional state. At first, Scotus rejects the theories that consider universals only in the mind and only in the world. He stands in the middle of these two. With two ideas, the common nature goes out from its pureness: non-numerical identity and commonness. The first refers to the idea that everything that has a real identity hasn’t a numerical identity. The real identity of nature exists from the pure state, and, at the same time, it is not an objective nature. But it seems to be in the mind while it is a conceptual issue. Thus, Scotus explains commonness as opposed to universality. Considering this idea, he says that commonness belongs to actual quiddity, not to quiddity in the intellect or mind. It is noticed that two interpretations be possible from the actual quiddity; the first is the objective quiddity, and the second is the quiddity Scotus has proved, i.e, the absolute quiddity that has someplace in the world, but not a sensual object. The commonness belongs to the second interpretation. The reason why the quiddity has commonness is the quiddity itself.Scotus represents the Aristotelian version of universals. He believes that human knowledge achieves experience and separation from particulars. Cognition is divided into sensual and intellectual aspects. The beginning of cognition is sensual but it results in an intellectual path. These are the general roles of the mind. But non-numerical identity and commonness are particularly mental acts. The separation of common nature’s features is by seeing the objective order. The non-numerical identity is obtained by considering the numerical identity. Also, commonness is obtained by considering the real quiddity. Concerning the above explanations, Scotus sees the particulars’ features as real or non-numerical identities and the common features as commonness.Both philosophers believe in active and passive roles of the mind. But, the reading of the mind’s activity is different. Scotus thinks like Aristotle, i.e, perceptions are just obtained from particulars. But Suhrawardi confirms that the mind makes some concepts without world interference, which means some of the universals are made only by the mind. While Scotus believes in the Aristotelian version of universals, Suhrawardi expresses both versions of the universals, although he does not make any connection between the two versions. It is to say that their ways for the explanation of universals are different, but they consider theories on the common and special features of the world. Suhrawardi expresses the light as the special feature and the quiddity (i.e, diversity of quiddity) as the common one, and Scotus proves the real identity (or non-numerical) as the special feature and the commonness (in front of pure universality) as the common one.